Using isolation-by-distance to jointly estimate effective population density and dispersal distance: a practical evaluation using bumble bees - Dylan T. Simpson (Oecologia, 2025)
Effective population density and intergenerational dispersal distance are key aspects of population biology, but obtaining empirical estimates of these parameters can be difficult. This is especially true for my study taxa, wild bees. In this paper, I apply and evaluate an existing but underutilized method to estimate effective density and dispersal distance of bumble bees ( Bombus , Apidae). Specifically, using 10 datasets of bumble bees in North America, I use the relationship between genetic isolation-by-distance and Wright’s neighborhood size to define a density-dispersal isocline—that is, a curve describing pairs of density and dispersal values consistent with observed rates of isolation-by-distance. These parameters are inversely related; as one increases the other decreases. I then use outside estimates of bumble bee dispersal distances to make more specific estimates of effective colony density. Compared to some prior estimates of census density (100s to 1000s colonies/km 2 ), my estimated effective colony densities were very low (1–41 effective colonies/km 2 ). I also hypothesize, however, that these estimates are affected by the spatial extent of sampling, due to scale-dependent patterns in the distribution of individuals. To test this hypothesis, I subsampled each dataset to simulate varying study extent, and repeated my analysis. Within populations, effective densities tended to decrease when measured across larger spatial extents. Altogether, I demonstrate a useful and under-appreciated tool for studying population biology, especially of small, mobile animals like bees, but also show that researchers must interpret their results carefully within the context of their study design.

Geometric effects of fragmentation are likely to mitigate diversity loss following habitat destruction in real‐world landscapes - Colleen Smith; Juan A. Bonachela; Dylan T. Simpson; Natalie J. Lemanski; Rachael Winfree (Global Ecology and Biogeography, 2024)
Aim Habitat conversion is the number one threat to biodiversity. The loss of biodiversity due to habitat loss might be exacerbated if species are harmed by fragmentation per se—the breaking apart of natural habitat that remains (hereafter fragmentation ). However, the evidence that species are harmed by habitat fragmentation is mixed. Studies at the patch scale tend to show that fragmentation reduces diversity due to negative demographic effects on species' dispersal, survival and fecundity. In contrast, studies at the landscape scale tend to show that fragmentation increases diversity. This discrepancy may be partly due to geometric effects, defined as greater species turnover between patches in more fragmented landscapes. Although these effects have been demonstrated theoretically and are expected to be stronger across larger spatial extents, it is unclear whether they are likely to occur in real‐world settings with both realistic landscape patterns and communities. Here, we investigated the possibility of geometric effects using simulations combined with real‐world landscape and community data. Location New Jersey, northeastern USA. Time period Current. Taxa studied Bees. Methods We focused on landscape sizes within the typical range for protected areas (36–576 ha), simulated forest loss using real landscape patterns, and simulated forest‐bee communities based on field data we collected. Results We found weak but positive effects of fragmentation: immediately following forest destruction, the most fragmented forests harboured up to 7.3% more species than the least fragmented forests of the same area, in agreement with observational studies of biodiversity along fragmentation gradients. In contrast to expectations, however, the overall effects of fragmentation did not change with spatial extent. Conclusions Our results suggest that fragmentation can mitigate biodiversity loss immediately following habitat destruction, but that the benefits do not vary strongly with spatial extent in real‐world landscapes and at extents relevant to land management.